Tackling antimicrobial resistance in Bangladesh: A scoping review of policy and practice in human, animal and environment sectors - Hoque, Roksana; Ahmed, Syed Masud; Naher, Nahitun; Islam, Mohammad Aminul; Rousham, Emily K.; Islam, Bushra Zarin; Hassan, Shaikh (PLOS ONE, 2022)
This article was published in Plos One [ © 2020 Hoque et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.] and the definite version is available at: https://doi.org/10.1371/journal.pone.0227947 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0227947